Diurnal Variation in Grapevine Water Stress as a Function of Changing Soil Water Status and Meteorological Conditions - van Zyl, J.L. (South African Journal of Enology and Viticulture, 2017)
The response of the grapevine cultivar Colombar to three irrigation treatments viz., (1) a well-watered control (2) soil water depletion to 25% plant available water (PAW) and (3) wetting of only the upper 50% of the root zone, was investigated during the ripening stage. Diurnal fluctuations in leaf water potential (LWP), stomatal resistance (Rs) and photosynthetic activity (PA) were determined weekly and relationships with meteorological factors calculated. Water potential gradients existed between sunlit leaves, shaded leaves, bunches and soil. It is suggested that this is a driving force which creates water movement from bunches to leaves during daytime and from soil to bunches at night, thus explaining increased water use of vines with increased crop level. Diurnal changes in LWP and PA were best correlated with leaf temperature (r=0,95) and photosynthetic active radiation (r=O, 74) respectively. During daytime, stomata remained open until a threshold leaf water potential of -1600 kPa was reached. All plant parameters responded to increased water stress due to soil water depletion, but vines subjected to a reduction in the depth of wetting, showed no stress throughout the experiment. Pre-dawn LWP was the most sensitive indicator of the onset of water stress which occurred at a soil water potential (SWP) of -64 kPa and a corresponding 42% PAW in the soil. Pre-dawn LWP correlated highly with SWP (r=0,95) and soil water content (r=0,89).